Monoacylglycerol Lipase Inhibitor MJN110 Reduces Neuronal Hyperexcitability, Restores Dendritic Arborization Complexity, and Regulates Reward-Related Behavior in Presence of HIV-1 Tat - League, Alexis F.; Gorman, Benjamin L.; Hermes, Douglas J.; Johnson, Clare T.; Jacobs, Ian R.; Yadav-Samudrala, Barkha J.; Poklis, Justin L.; Niphakis, Micah J.; Cravatt, Benjamin F.; Lichtman, Aron H.; Ignatowska-Jankowska, Bogna M.; Fitting, Sylvia (Frontiers in Neurology, 2021)
While current therapeutic strategies for people living with human immunodeficiency virus type 1 (HIV-1) suppress virus replication peripherally, viral proteins such as transactivator of transcription (Tat) enter the central nervous system early upon infection and contribute to chronic inflammatory conditions even alongside antiretroviral treatment. As demand grows for supplemental strategies to combat virus-associated pathology presenting frequently as HIV-associated neurocognitive disorders (HAND), the present study aimed to characterize the potential utility of inhibiting monoacylglycerol lipase (MAGL) activity to increase inhibitory activity at cannabinoid receptor-type 1 receptors through upregulation of 2-arachidonoylglycerol (2-AG) and downregulation of its degradation into proinflammatory metabolite arachidonic acid (AA). The MAGL inhibitor MJN110 significantly reduced intracellular calcium and increased dendritic branching complexity in Tat-treated primary frontal cortex neuron cultures. Chronic MJN110 administration in vivo increased 2-AG levels in the prefrontal cortex (PFC) and striatum across Tat(+) and Tat(-) groups and restored PFC N-arachidonoylethanolamine (AEA) levels in Tat(+) subjects. While Tat expression significantly increased rate of reward-related behavioral task acquisition in a novel discriminative stimulus learning and cognitive flexibility assay, MJN110 altered reversal acquisition specifically in Tat(+) mice to rates indistinguishable from Tat(-) controls. Collectively, our results suggest a neuroprotective role of MAGL inhibition in reducing neuronal hyperexcitability, restoring dendritic arborization complexity, and mitigating neurocognitive alterations driven by viral proteins associated with latent HIV-1 infection.